"What Innocent Bystanders?": The Impact of Law and Economics Reasoning on Rural Property Rights - Wiber, Melanie G. (Anthropologica, 2022)
In May 2004, the Supreme Court of Canada denied the Saskatchewan farmer Percy Schmeiser innocent bystander status and ruled in favour of protecting the intellectual property rights of Monsanto, which holds a patent on genetically modified canola seed. Farmers around the world have protested this decision as an attack on their privileged position under national patent legislation, fueling a larger debate about biotechnology, farmer seed systems and intellectual property rights. This article looks at the patent infringement arguments in Canada in the context of the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS) and of potential amendments to the Canada Patent Act. Law and economics scholars have critiqued both "innocent bystander" and "farmer autonomy" as legitimate defenses in such cases of patent infringement. In the process, they have ignored, and perhaps facilitated, wider issues of property transformations in the rural setting.